Communication Management in Diversity Tolerance to Maintain The Unity of The People - Sutisna; Khori, Ahmad (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This article aims to identify the importance of communication management as a multidimensional approach encompassing managerial, operational, reflective, and strategic functions within organizations to ensure effective coordination, resolve communication crises, and achieve organizational goals. Focusing on the context of pluralism in Indonesia, the article explores the role of communication in maintaining social harmony through tolerance of diversity while reducing identity- and distribution-based conflicts. The novelty of this study lies in integrating communication management concepts with strategies to enhance multicultural attitudes through education, particularly in addressing globalization challenges that foster individualism and weaken social cohesion. Key findings indicate that effective communication management is crucial in promoting positive relationships within organizations and ensuring timely and accurate information delivery. This management approach boosts efficiency and productivity and fosters tolerance, conflict resolution, and social inclusion. Tolerance of diversity, including respect for differences in race, religion, gender, sexual orientation, and other backgrounds, plays a vital role in creating an inclusive culture and peaceful environment. Furthermore, maintaining the unity of the ummah is essential for preventing conflicts and fostering harmony through understanding, cooperation, and respect for differences. These findings highlight the need for integrating communication management, tolerance promotion, and efforts to sustain unity to build a more stable and prosperous society. Future research is recommended to explore the application of digital technologies in supporting communication management, develop culturally based tolerance strategies, and evaluate the impact of multicultural education on social harmony.